Organisation und Bildung für nachhaltige Entwicklung: Eine kritische Bestandsaufnahme der Konzeptionalisierung organisationalen Lernens im BNE-Diskurs - Elven, Julia (Gruppe. Interaktion. Organisation., 2022)
The paper at hand is published in the journal Gruppe. Interaktion. Organisation. (GIO) and proposes an organizational research perspective on Education for Sustainable Development (ESD) by drawing on concepts of organizational learning. To this end, the results of a (quantitative) systematic review are used to identify shortcomings and blind spots in the research discourse. Thereafter, conceptual connections and potentials of a theoretical reconstruction of sustainability-related educational processes will be pointed out in order to finally argue for the extension of the ESD discourse by organizational-educational perspectives.
CRIS-Team Scopus Importer:2022-12-09
Keywords: Education for sustainable development; Organizational education; Organizational learning; Systematic review